Thermal Properties Characterization of Glass Fiber Hybrid Polymer Composite Materials - B Vaggar, Gurushanth; C Kamate, S; V Badyankal, Pramod (International Journal of Engineering and Technology, 2018)
In the current work characterization of thermal properties are find out to the prepared specimens of silicon filler hybrid composite materials (silicon filler glass â€“ fiber chop strand). The specimens were prepared by hand layup followed by compression molding machine by non-heating molding technique. Thermal conductivity (K), Coefficient thermal expansion (CTE) and Thermal gravimetric analysis (TGA) are found by composite slab method and by thermal muffler oven in a laboratory. The guard heater is used to supply heat which is measured by voltmeter and ammeter. Thermocouples are placed between the interface of the copper plates and the specimen of silicon filled hybrid polymer composite material (HPC), to read the temperatures. By the experimental readings it is found that the K of silicon filler hybrid composite material directly proportional to the % of silicon fillers for the different trails. The CTE inversely varies with % of silicon fillers and in thermal gravimetric analysis the failure of material takes place at 300Â°C for a time of 20 minutes and also reduction in mass of silicon inserted hybrid composite material. From the results it has been concluded that the considerable enhance in thermal conductivity with negligible decrease in CTE and increase in thermal resistivity of hybrid composite materials.Â Â